1983
DOI: 10.1111/j.1540-5915.1983.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Education TEAM‐SIZE EFFECTS ON BUSINESS GAME PERFORMANCE AND DECISION‐MAKING BEHAVIORS

Abstract: The effects of various decision-making team sites in a complex business game were studied. Firm size was .ssoCiated with nonlinear performance results and decision curves resulting in differential leaning outcoma. learning sources, attrition rates. and decisionmaking behaviors. A threemember format produced the highat learning levels while twom e m k f m s expaienced only marginally signifmt knowledge incrurses. Single-member f m experienced the most bankruptcies and dropouts. A contingency view of gaming effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 18 publications
0
17
1
1
Order By: Relevance
“…O'Reilly (1982), in a field study regarding the use of information sources, found that as the quality and accessibility of information sources increase, so does the frequency of Smith (1979), Gray (1972) GPA teams and performance Dill (1961), Vance and Gray (1967) No relationship between GPA and performance Wolfe and Box (1988) Significant relationship between GPA and cohesion Group size Wolfe and Chacko (1983) Four-member teams outperformed one-and two-member teams Gentry (1980) Larger teams perform better Process variable Cohesion McKenney and Dill (1966);Deep, No relationship between cohesion Bass, and Vaughan (1967) and performance Norris and Niebuhr (1980), Miesing Cohesive teams perform better (1982) Conflict Affisco and Chanin (1990) No difference in conflict between DSS and non-DSS groups Chanin and Schneer (1984) Personality related to conflict handling behavior Information usage Schroeder and Benbasat (1975), Information usage increases with O' Reilly (1982) increase in environmental uncertainty their use. This research also confirmed the Schroeder and Benbassat finding that information usage increases with an increase in environmental uncertainty.…”
Section: Group Processesmentioning
confidence: 96%
See 1 more Smart Citation
“…O'Reilly (1982), in a field study regarding the use of information sources, found that as the quality and accessibility of information sources increase, so does the frequency of Smith (1979), Gray (1972) GPA teams and performance Dill (1961), Vance and Gray (1967) No relationship between GPA and performance Wolfe and Box (1988) Significant relationship between GPA and cohesion Group size Wolfe and Chacko (1983) Four-member teams outperformed one-and two-member teams Gentry (1980) Larger teams perform better Process variable Cohesion McKenney and Dill (1966);Deep, No relationship between cohesion Bass, and Vaughan (1967) and performance Norris and Niebuhr (1980), Miesing Cohesive teams perform better (1982) Conflict Affisco and Chanin (1990) No difference in conflict between DSS and non-DSS groups Chanin and Schneer (1984) Personality related to conflict handling behavior Information usage Schroeder and Benbasat (1975), Information usage increases with O' Reilly (1982) increase in environmental uncertainty their use. This research also confirmed the Schroeder and Benbassat finding that information usage increases with an increase in environmental uncertainty.…”
Section: Group Processesmentioning
confidence: 96%
“…Research on group size has shown that 4-member groups learn more from business games when compared to 1-or 2-member groups (Wolfe & Chacko, 1983). Comparing performance of 2-, 3-, and 4-member teams, it was found that larger teams perform better.…”
Section: Contextual Variablesmentioning
confidence: 97%
“…The team size is an indicator for the effort of team coordination [50]. While smaller teams located in a single room can directly communicate the need for formalization increases if the team grows (also if distributed/virtual teams become relevant).…”
Section: Sizementioning
confidence: 99%
“…It has been shown that simulation playing teams with strong task orientation perform better than teams that are more focused on rules or social aspects (Hunger & Wheelen, 1975). The role of attitudes and their effects on the performance of teams has also been a topic (Glazer et al, 1987), as have the effect of leadership style and size of team to simulation performance (Wolfe & Chacko, 1983). Moreover, it has been detected that the complexity of the simulation has an effect on performance (Lainema & Lainema, 2007).…”
Section: Decision-making Studies In Business Simulation Game Contextmentioning
confidence: 99%